Vortex Generation and Aeroacoustics in Asymmetric Wakes - Mathias, Marlon Sproesser; Gennaro, Elmer Mateus; Medeiros, Marcello A.F. (Elsevier, 2015)
High-lift devices in an aircraft are important sound generators. These devices should be studied in order to further reduce overall aircraft noise. The high-lift devices operating at a high angle of attack promote the formation of large wakes. Owing to the generation of lift these wakes are asymmetric. A model has been proposed to investigate the sound generation and the vorticity dynamics in a two-dimensional asymmetric wake profile under spatial development. A DNS code was developed for this purpose and the investigation was based on direct numerical simulations of a two-dimensional compressible flow. The results indicated a significant increase in sound level due to vortex pairing which occurs after a substantial vortex deformation.
Keywords: Aeroacoustics; Asymmetric wake; DNS; Vortex pairing